1996
DOI: 10.1002/(sici)1096-9861(19960930)373:4<575::aid-cne7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Afferent connections to the dorsal nucleus of the lateral lemniscus of the mustache bat: evidence for two functional subdivisions

Abstract: The dorsal nucleus of the lateral lemniscus (DNLL) of the mustache bat, Pteronotus parnellii, was found to consist of two divisions. The neurons in each division were distinguished by their temporal discharge patterns evoked both by tone bursts and sinusoidal amplitude-modulated (SAM) signals. Neurons in the anterior one-third of the DNLL responded to tone bursts with an onset discharge pattern and only phase-locked to SAM signals with low modulation frequencies (< 300 Hz). Neurons in the posterior two-thirds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…They are also the dominant type in the dorsal nucleus of the lateral lemniscus (DNLL), a nucleus the neurons of which are almost exclusively GABAergic (Brugge et al, 1970;Adams and Mugniani, 1984;Covey, 1993; Yang and Pollak, 1994a,b,c;Winer et al, 1995). The DNLL, like the ICc, is one of the principal targets of both the ipsilateral and contralateral LSOs (Glendenning et al, 1981;Ross et al, 1988;Shneiderman et al, 1988Shneiderman et al, , 1999Yang et al, 1996). The DNLL, in turn, sends strong GABAergic projections bilaterally to the ICc (Ross et al, 1988;Shneiderman et al, 1988Shneiderman et al, , 1999Gonzalez-Hernandez et al, 1996;Kelly et al, 1998).…”
mentioning
confidence: 89%
“…They are also the dominant type in the dorsal nucleus of the lateral lemniscus (DNLL), a nucleus the neurons of which are almost exclusively GABAergic (Brugge et al, 1970;Adams and Mugniani, 1984;Covey, 1993; Yang and Pollak, 1994a,b,c;Winer et al, 1995). The DNLL, like the ICc, is one of the principal targets of both the ipsilateral and contralateral LSOs (Glendenning et al, 1981;Ross et al, 1988;Shneiderman et al, 1988Shneiderman et al, , 1999Yang et al, 1996). The DNLL, in turn, sends strong GABAergic projections bilaterally to the ICc (Ross et al, 1988;Shneiderman et al, 1988Shneiderman et al, , 1999Gonzalez-Hernandez et al, 1996;Kelly et al, 1998).…”
mentioning
confidence: 89%
“…Principal cells in the medial superior olive (MSO), the lateral superior olive (LSO), and the cochlear nuclei have unique response patterns and are primary sources of ascending inputs to the DNLL (Casseday et al 1988;Glendenning et al 1981;Shneiderman et al 1988;Vater et al 1995;Yang et al 1996). Shneiderman et al (1988) showed that the afferent axons from these sources to the DNLL are distributed in horizontal bands and have a tonotopic organization.…”
Section: Origins Of the Unit Typesmentioning
confidence: 99%
“…It receives roughly the same complement of ascending inputs as the IC including projections from the contralateral cochlear nucleus, the ipsilateral medial superior olive, and both lateral superior olives (Casseday et al 1988; Glendenning et al 1981;Shneiderman et al 1988;Vater et al 1995;Yang et al 1996). It also receives a heavy input from the contralateral DNLL by the commissure of Probst (Glendenning et al 1981; Iwahori 1986;Oliver and Shneiderman 1989;Shneiderman et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations